2019
DOI: 10.1101/670554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Histone deacetylase 1 (HDAC1) and HDAC2 enhances CRISPR/Cas9 genome editing

Abstract: Despite the rapid development of CRISPR/Cas9-mediated gene editing technology, the gene editing potential of CRISPR/Cas9 is hampered by low efficiency, especially for clinical applications.One of the major challenges is that chromatin compaction inevitably limits the Cas9 protein access to the target DNA. However, chromatin compaction is precisely regulated by histone acetylation and deacetylation. To overcome these challenges, we have comprehensively assessed the impacts of histone modifiers such as HDAC (1-9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A further study performed by Riesenberg and Maricic 20 showed that HDACi-induced activation of Cas9 was indeed observed only in a modified version of Cas9 protein, called Cas9 nickases (Cas9n). Liu et al 19 systematically compared effects of various HDACi and found that HDAC1/2 inhibitors might sustain the editing effect of CRISPR-Cas9. Meanwhile, HDAC3 inhibitor rather reduced Cas9 activity, 19 suggesting a complicated role of HDAC and HDACi in CRISPR-Cas9-mediated genome editing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further study performed by Riesenberg and Maricic 20 showed that HDACi-induced activation of Cas9 was indeed observed only in a modified version of Cas9 protein, called Cas9 nickases (Cas9n). Liu et al 19 systematically compared effects of various HDACi and found that HDAC1/2 inhibitors might sustain the editing effect of CRISPR-Cas9. Meanwhile, HDAC3 inhibitor rather reduced Cas9 activity, 19 suggesting a complicated role of HDAC and HDACi in CRISPR-Cas9-mediated genome editing.…”
Section: Discussionmentioning
confidence: 99%
“…Because the change of environmental pH-value impacts the nature of the protein, 16 I measured the absorption of pH indicator (phenol red) in medium treated with increasing concentrations of VPA and could not detect the pH variation even at the highest concentration (100 mM, Figure S2A). Considering that VPA is a well-known histone deacetylase inhibitor (HDACi) and the influence of HDACis on the activity of CRISPR-Cas9 system has been reported, [17][18][19][20] In an effort to evaluate VPA-induced degradation of SpyCas9 protein in living cells, I overexpressed SpyCas9 using a commercial CRISPR vector, carrying a cytomegalovirus (CMV)-driven SpyCas9-GFP expression cassette (refer to Cas9 GFP ) and gRNA sequence, which is designed not to recognize any sequence in human cells. Results obtained from immunoblotting showed that VPA was the single HDACi able to destabilize SpyCas9 protein under hyperthermia conditions (39.5 C; Figure 2B; Figure S2C), which was confirmed by fluorescence-activated cell sorting (FACS) analysis; GFP-positive cells were significantly reduced from 50% to 25% in the presence of VPA (10 mM; Figure 2C; Figure S2D).…”
Section: Vpa Destabilizes Spycas9 Protein In Cellsmentioning
confidence: 99%
“…The sequential ChIP-qPCR has been described elsewhere [20][21][22] . Cells were grown in a T175 cell culture flask to 90% confluency.…”
Section: Sequential Chromatin Immunoprecipitation (Sequential Chip)mentioning
confidence: 99%
“…Primers are listed in Supplementary Table S1. The qPCR amplifications have been described elsewhere 22 .…”
Section: Sequential Chromatin Immunoprecipitation (Sequential Chip)mentioning
confidence: 99%
“…It is well established that the integration of Cas9 into the target locus is influenced by many factors, such as sequences in and around the target, sgRNA sequences, and cell types (Miyaoka et al, 2016;Cai et al, 2019). In addition, it has been revealed that the chromatin accessibility is a major determinant of Cas9 binding (Wu et al, 2014;Horlbeck et al, 2016;Isaac et al, 2016;Yarrington et al, 2018;Liu et al, 2019Liu et al, , 2020. In nondividing cells, the chromatin dynamics may be more relative static.…”
mentioning
confidence: 99%